The ISPAInt Injury Prevention Programme for Youth Competitive Alpine Skiers: A Controlled 12-Month Experimental Study in a Real-World Training Setting - Schoeb, Thierry; Fröhlich, Stefan; Frey, Walter O.; Verhagen, Evert; Farshad, Mazda; Spörri, Jörg (Frontiers in Physiology, 2022)
Evidence-based injury prevention programmes for youth competitive alpine skiers are widely absent. The aims of this controlled 12-month experimental study were to introduce a novel injury prevention programme targeted to the injury patterns of youth skiers, called ISPAInt, and to compare the differences in injury occurrence between an intervention group (IG) additionally performing the ISPAInt programme and an independent, historical control group (CG) following their regular training routines. None of the skiers of the CG were part of the IG and vice versa. The study was directly conducted within the real-world youth development structures of skiers competing at the under 16 years (U16) level in Switzerland. Seventy-one skiers (aged 14.4±0.3 years) assigned to the IG were compared to 58 age- and gender-matched controls. The IG was offered the ISPAInt programme with the recommendation to perform it at least once per week. Skiers' adherence to this recommendation was surveyed but not enforced. Injuries were recorded using the Oslo Sports Trauma Research Centre Questionnaire. Primary outcomes were the absolute injury rates (number of injuries/100 athletes per season) and epidemiological incidence proportion (number of injured athletes/100 athletes per season). The secondary outcome was the average two-weekly prevalence of traumatic knee, knee overuse and lower back overuse injuries. There were lower absolute rates of all traumatic injuries (rate/risk difference, RD: -57.1 (-98.1, -16.0); rate/risk ratio, RR: 0.665 (0.485, 0.884)) and overuse injuries (RD: -35.9 (-71.0, -0.7); RR: 0.699 (0.493, 0.989)) in the IG than in the CG. Likewise, the epidemiological incidence proportion for all overuse injuries was smaller in the IG (RD: -28.4 (-44.8, -12.0); RR: 0.598 (0.435, 0.822)), while the proportion of skiers suffering from traumatic injuries did not significantly differ between the groups. Notably, the IG particularity differed from the CG in the average two-weekly prevalence of knee trauma, knee overuse and lower back overuse complaints, three of the major injury-related hot spots in youth skiers. Based on these promising results, the ISPAInt programme may have great potential to prevent injuries in youth competitive alpine skiers, and the underlying exercises should be considered complementary training content at the U16 level.